A forja do profissional da guerra: dois séculos de formação do oficial combatente do Exército Brasileiro - Elton Licério Rodrigues Machado (Navigator)
The present study has the scope of perceiving the social, politcal, cultural and pedagogical conceptions that have guided the changes through which the combating officer has gone as well as the implications of such processes. Its reference basis are the different sites where the training course for the combating officer of the Brazilian Army took place. After an exploratory research, the arising problems and the solutions implanted to overcome the dichotomy related to the officer training became evident. Therefore, the several reforms in the military education carried out by military leaders over the years had the objective of breaking such segregation and promote harmony between the scientific academic training and the technical professional training.